Barstool consequences: college students' risk perceptions when interacting with Barstool Sports' modeling of the college experience through Instagram - Coviello, Jenna, author; Faw, Meara, advisor; Marx, Nicholas, committee member; Barone, Ryan, committee member (Colorado State University. Libraries, 2019)
This study focuses on how college students engage with the various Instagram accounts run by Barstool Sports (e.g., @chicks, @barstoolsports, @5thyear, and college-affiliated Barstool Instagrams) and how engagement influences their perceptions of risk and risky behavior decision-making. Through this study, I review the literature surrounding Social Cognitive Theory (SCT) and risk communication. I also give an overview of Barstool Sports and how they present college students in the previously mentioned Instagram accounts. I looked to answer two research questions: RQ1: How does Barstool's affiliated Instagram accounts showcasing college-student-produced videos model destructive and risky behaviors? RQ2: How do Barstool Sports' Instagram accounts influence college-aged consumers' perceptions of risk and decision making in the college experience? I conducted fifteen interviews with recent college graduates of universities who have previously consumed and/or currently consume media with Barstool Sports' affiliation. My goal was to understand how participants' consumption of this media specifically affects their cognitive development, risk perceptions, and, ultimately, the culture of their college institution. I coded the interviews through thematic analysis and discovered three, key themes in RQ1: Glorifying college stereotypes as the "norm," imitation and "one upping" to be featured, and college life as opportunity for Barstool content causes a need to be vigilant of one's actions. Five, key themes were uncovered in RQ2: Being featured on Barstool and consuming Barstool for "coolness," popularity, and social clout; dissonance from personal morals; cringy and risky images provide entertainment, but to a certain extent; recognition of the unexpected (and sometimes expected) negatives of Barstool features and a student's selective disengagement and its association to a college's mission and conduct expectation. Because college is a time when students run the risk of developing negative habits that can damage their academic standing, negatively impact their health, and result in struggles with university student conduct codes, this research can provide clarity on why students choose to partake in the behaviors and actions like those portrayed on these Instagram accounts.
Keywords: Instagram; social cognitive theory; undergraduate students; risk communication; decision-making; social media consumption